A landscape approach to advance intermittent river ecology. (1st February 2016) - Datry, Thibault; Pella, Herve; Leigh, Catherine; Bonada, Núria; Hugueny, Bernard
Summary: Intermittent rivers are increasingly viewed as shifting mosaics of lotic (flowing water), lentic (standing water) and terrestrial (dry riverbed) habitats. The diversity, spatial arrangement, temporal turnover and connectivity of these habitats are controlled by the magnitude, frequency, duration and extent of drying and rewetting events, which maintain habitat heterogeneity and control biodiversity and biogeochemical processes in intermittent rivers. We consider intermittent rivers as spatiotemporal landscape mosaics to identify the implications such a view has for empirical and theoretical developments in landscape and river ecology. Using observational data of flow states collected by citizen scientists along 1400 km of river channels in western France, we used landscape metrics and ecologically scaled indices for four hypothetical, aquatic species (two fish and two insects) to describe the dynamics of intermittent river mosaics for five catchments. Dry patches dominated most observation dates but flowing patches had the longest average length and occupied the greatest proportion of channel length. At the start of each summer, catchments were almost entirely composed of flowing patches but lentic and dry patches could represented up to 80% of the catchments as summer progressed. Patch dynamics were typified by high levels of spatiotemporal variability. In contrast, ecologically scaled indices did not vary greatly among catchments within species. The ecologically scaled indices representing small fish were the most affected by habitat fragmentation. Such a landscape perspective could affect understanding of biodiversity patterns and biogeochemical processes in intermittent rivers. We outline the methodological developments required to integrate landscape approaches into intermittent river research, the associated challenges and current limitations in landscape ecology tools and models and the benefits of citizen science data sets. The continued quantification of shifting habitat mosaics in intermittent rivers will provide multiple opportunities to advance river and landscape ecology.